Evidence for H-bonding interactions to the μ-η2:η2-peroxide of oxy-tyrosinase that activate its coupled binuclear copper site - Kipouros, Ioannis; Stańczak, Agnieszka; Culka, Martin; Andris, Erik; Machonkin, Timothy R; Rulíšek, Lubomír; Solomon, Edward I (Chemical communications (Cambridge, England), 2022)
The factors that control the diverse reactivity of the μ-η2:η2-peroxo dicopper(II) oxy-intermediates in the coupled binuclear copper proteins remain elusive. Here, spectroscopic and computational methods reveal H-bonding interactions between active-site waters and the μ-η2:η2-peroxide of oxy-tyrosinase, and define their effects on the Cu(II)2O2 electronic structure and O2 activation.
Keywords: peroxidy; Copper; Peroxides; spektrální analýza; Monophenol Monooxygenase; katalytická doména; Oxygen; tyrosinasa; Catalytic Domain; kyslík; Spectrum Analysis; měď